A fish kill related to an acid-metal spill (Little Sackville River, Nova Scotia, Canada) - Conrad, Cathy (Revue des sciences de l'eau / Journal of Water Science, 2008)
AbstractThis paper documents the aqueous transport of acidic drainage in the Little and Main Sackville Rivers in Nova Scotia, and contributes to a better general understanding of the movement and duration of impact in such an event. Acidic drainage has been often noted as a major environmental hazard in mainland Nova Scotia. In addition to the details of the distribution and dispersal of metal concentrations in the Sackville Rivers ecosystem, some of the effects upon the aquatic organisms in the area are presented.Both an automated and hand-held devices were used to obtain physical water quality both prior to and after the event. The environmental impacts of the contaminant are discussed in terms of their immediate effects. The immediate effects in the mixing zone, where toxicity occurred, were at the entrance of the acid-bearing outflow, where there was a presence of mixing with the higher pH waters in the main channel. More than 4000 dead fish were counted (including approximately 300 American eels (Anguilla rostrata), 1000 one-year-old salmon (Salmo salar), 150 two-year-old salmon, 24 small-mouth bass (Micropterus dolmieui) and 24 suckers (Catostomus commersonii), in addition to minnows (specific species unidentified), small gaspereau (Alosa pseudoharengus), brook trout (Salvelinus fontinalis), freshwater mussels (specific species unidentified), and a snapping turtle (Chelydra serpentina). It is most likely that the fish kill resulted from rapid suffocation due to metal flocculants clogging the gills. It was in this zone where dissolved metals precipitated (Al, Fe, Cu).